Strengthening the Role of Village Head Communications In The Digital Age - Andre Novie Rahmanto, Edy Sutrisno, Ismi Dwi Astuti Nurhaeni dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The village head as a local actor has a strategic role in the development andempowerment of village communities. The implementation of Law No. 6 of 2014on Villages as well as Law Number 14 Year 2008 on PublicInformation Transparency is a demand that must be responded by the village head.Moreover, the third point of Nawacita: "Building Indonesia from the Fringe byStrengthening Areas and Villages within the Framework of Unitary State"places the village as a Government development priority. On the other hand, themassive development of digital media influences the communication patterns ofsociety. But there is still reluctance from the village head to take advantageof digital communication media as a new media. Denis McQuail outlines themain features of new media that can be utilized such as decentralization, highability, interactivity and flexibility of forms, content and usage. ParticipatoryMedia Culture Theory by Henry Jenkins is used to view social realities inwhich new media offer the audience to jointly take on the role of mediaconsumers and media producers alike. Through the literature study, this articledescribes how efforts can be made to strengthen the role of village headcommunications in the digital age.Keywords: [the Village Head, New Media, Participatory Media Culture, Source of Credibility]